2023
DOI: 10.2196/43636
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Bias Modification Training Targeting Fatigue in Patients With Kidney Disease: Usability Study

Abstract: Background Fatigue is an important symptom for many patients, including patients with kidney disease. Cognitive biases, such as attentional bias and self-identity bias, are thought to influence fatigue. Cognitive bias modification (CBM) training is a promising technique to counter fatigue. Objective We aimed to evaluate a CBM training among patients with kidney disease and health care professionals (HCPs) and assess acceptability and applicability in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 59 publications
(67 reference statements)
0
0
0
Order By: Relevance
“…Both of these studies evaluated the application with multiple stakeholders (patients and health care professionals) and revealed positive results. Although in this usability study with people suffering from breast-cancer, preliminary data analyses only revealed a trend in altering self-identity bias (33), a pilot study with people suffering from chronic kidney disease revealed strong CBM effects on cognitive bias, and promising results on symptoms and related behaviour (34).…”
Section: Background Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Both of these studies evaluated the application with multiple stakeholders (patients and health care professionals) and revealed positive results. Although in this usability study with people suffering from breast-cancer, preliminary data analyses only revealed a trend in altering self-identity bias (33), a pilot study with people suffering from chronic kidney disease revealed strong CBM effects on cognitive bias, and promising results on symptoms and related behaviour (34).…”
Section: Background Introductionmentioning
confidence: 61%
“…Next, following the iterative human-centred design framework (32), our research team has investigated this novel eHealth application by researching usability. This has been done with people suffering from breast cancer (33) and from chronic kidney disease (34). Both of these studies evaluated the application with multiple stakeholders (patients and health care professionals) and revealed positive results.…”
Section: Background Introductionmentioning
confidence: 99%
“…To get a better understanding of the potential mechanistic role of information processing biases, longitudinal studies are needed that change these biases and assess any corresponding change in symptom experience. Recently, promising steps have been made to develop Cognitive Bias Modification training to reduce fatigue in kidney patients (Geerts et al, 2023). It would be interesting to study if the implicit IB is moderated via existing treatments such as cognitive behavioural therapy for MS-related fatigue, in which cognitions and attentional processes are explicitly addressed.…”
Section: Clinical Implications and Future Researchmentioning
confidence: 99%